Small-Molecule-based Supramolecular Plastics Mediated by Liquid-Liquid Phase Separation - Yu Jingjing; Qi Dawei; Mäkilä Ermei; Lassila Lippo; Papageorgiou Anastassios C.; Peurla Markus; Rosenholm Jessica M.; Zhao Zhao; Vallittu Pekka; Jalkanen Sirpa; Jia Chunman; Li Jianwei (WILEY-V C H VERLAG GMBH, 2022)
Plastics are one of the most widely used polymeric materials. However, they are often undegradable and non-recyclable due to the very stable covalent bonds of macromolecules, causing environmental pollution and health problems. Here, we report that liquid-liquid phase separation (LLPS) could drive the formation of robust, stable, and sustainable plastics using small molecules. The LLPS process could sequester and concentrate solutes, strengthen the non-covalent association between molecules and produce a bulk material whose property was highly related to the encapsulated water amounts. It was a robust plastic with a remarkable Young's modulus of 139.5 MPa when the water content was low while became adhesive and could instantly self-heal with more absorbed water. Finally, responsiveness enabled the material to be highly recyclable. This work allowed us to understand the LLPS at the molecular level and demonstrated that LLPS is a promising approach to exploring eco-friendly supramolecular plastics that are potential substitutes for conventional polymers.